2016
DOI: 10.1371/journal.pcbi.1005166
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Resonance in the Gerbil Medial Superior Olive

Abstract: A high-frequency, subthreshold resonance in the guinea pig medial superior olive (MSO) was recently linked to the efficient extraction of spatial cues from the fine structure of acoustic stimuli. We report here that MSO neurons in gerbil also have resonant properties and, based on our whole-cell recordings and computational modeling, that a low-voltage-gated potassium current, IKLT, underlies the resonance. We show that resonance was lost following dynamic clamp replacement of IKLT with a leak conductance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 41 publications
(117 reference statements)
3
8
0
Order By: Relevance
“…We therefore derived resonance frequencies for varying amplitudes I ( f ) of the ZAP stimulus (Figures 2A,B ; 14 neurons, 91 trials of P15 MSO; 12 neurons, 82 trials of >P60 MSO) and varying magnitudes I 0 of an additionally applied constant current (Figures 2C,D ; 10 neurons, 41 trials of P15 MSO; 10 neurons, 32 trials >P60 MSO). As previously described (Mikiel-Hunter et al, 2016 ), both an increase in amplitude and an increase in I 0 yielded generally larger resonance frequencies (Figures 2B,D ). The correlation between resonance frequency f r and amplitude was significant in all groups (Pearson's r = 0.71, p < 0.0001 for P15, n = 91 stimuli, r = 0.60, p < 0.0001 for P > 60, n = 82; r = 0.80, p < 0.0001 for both age groups, n = 173).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We therefore derived resonance frequencies for varying amplitudes I ( f ) of the ZAP stimulus (Figures 2A,B ; 14 neurons, 91 trials of P15 MSO; 12 neurons, 82 trials of >P60 MSO) and varying magnitudes I 0 of an additionally applied constant current (Figures 2C,D ; 10 neurons, 41 trials of P15 MSO; 10 neurons, 32 trials >P60 MSO). As previously described (Mikiel-Hunter et al, 2016 ), both an increase in amplitude and an increase in I 0 yielded generally larger resonance frequencies (Figures 2B,D ). The correlation between resonance frequency f r and amplitude was significant in all groups (Pearson's r = 0.71, p < 0.0001 for P15, n = 91 stimuli, r = 0.60, p < 0.0001 for P > 60, n = 82; r = 0.80, p < 0.0001 for both age groups, n = 173).…”
Section: Resultssupporting
confidence: 86%
“…In the initial data the depolarizing resonance frequency f r appeared to scatter over a large range for individual neuron types (Figure 1E ). In previous papers (Rotstein, 2015 ; Mikiel-Hunter et al, 2016 ), it was shown that f r increases with the average membrane depolarization indicating a non-linear voltage-dependent gating of the subthreshold conductances. Thus, we expected, that our observed scatter of f r can be explained by such factors as well.…”
Section: Resultsmentioning
confidence: 92%
“…The firing rate of the MSO model is of course strongly influenced by the balance between the excitatory inputs from the ANFs and the inhibitory inputs from the GBCs but it is additionally modulated by changes of the spiking thresholds. MSO neurons have been found to exhibit subthreshold resonance (Remme et al, 2014 ; Mikiel-Hunter et al, 2016 ) which introduces frequency dependent thresholds. The MSO model used in this study exhibited a resonance frequency at about 260 Hz (see Figure S2 ) which is in agreement with the resonance frequencies found in electrophysiological studies (Remme et al, 2014 ; Mikiel-Hunter et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…MSO neurons have been found to exhibit subthreshold resonance (Remme et al, 2014 ; Mikiel-Hunter et al, 2016 ) which introduces frequency dependent thresholds. The MSO model used in this study exhibited a resonance frequency at about 260 Hz (see Figure S2 ) which is in agreement with the resonance frequencies found in electrophysiological studies (Remme et al, 2014 ; Mikiel-Hunter et al, 2016 ). The reduced spiking threshold around 260 Hz in combination with the dynamics of the synaptic inputs results in a peak in MSO response seen in Figure 3F , which also corresponds to the peak in sensitivity shown in Figure 3D .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation